Poly[[μ-1,3-bis(pyridin-3-yl)urea]bis(μ4-glutarato)dicopper(II)] - Frederick C. Ezenyilimba; Robert L. LaDuca (IUCrData, 2023)
The title compound, [Cu2(C5H6O4)2(C11H10N4O)]n, contains square-pyramidally coordinated CuII ions linked by anti-gauche conformation glutarate (glu) ligands into [Cu2(glu)2]n di-periodic coordination polymer layers with embedded [Cu2(OCO)4] paddlewheel clusters. In turn, the layer motifs are connected by 1,3-di(pyridin-3-yl)urea (3-dpu) linkers to form a [Cu2(glu)2(3-dpu)]n tri-periodic coordination polymer network. Treating the [Cu2(OCO)4] clusters as 6-connected nodes reveals an underlying 41263 pcu topology according to TOPOSPRO software [Blatov et al. (2014). Cryst. Growth Des. 14, 3576–3586].